Pressure pain threshold of the cervico‐facial muscles in healthy elderly people: the role of gender, age and dominance. (10th February 2014) - De Rui, Marina; Marini, Ida; Bartolucci, Maria Lavinia; Inelmen, Emine Meral; Bortolotti, Francesco; Manzato, Enzo; Gatto, Maria Rosaria Antonella; Checchi, Luigi; Sergi, Giuseppe
Abstract : Objective: The aim of this study was to assess the impact of age on pressure pain threshold (PPT) of cervico‐facial muscles in healthy geriatric subjects and to investigate the role of gender and dominance on nociception. Background: Musculo‐skeletal pain is common in the elderly, but being subjective, it risks to be underdiagnosed and undertreated. A useful method for assessment of local pain is determining PPT through pressure algometry. Ageing process seems to increase PPTs, but reference values for the assessment of pain in geriatric subjects are lacking. Methods: In this study, PPTs in temporal muscle, masseter, sternocleidomastoid, occipital and splenius capitis of 97 healthy elderly subjects were measured using Fischer algometer. Participants were divided by age in four classes (years 65–69; 70–74; 75–79; ≥80). Results: Women had lower PPTs in all muscles compared with men. Comparing PPTs obtained from the right and the left side, no significant differences were recorded neither in men nor in women. When dividing subjects by age class and education, in both genders no significant differences were observed in PPTs among the groups, neither in the right nor in the left sides. Conclusion: In conclusion, the present study reports reference PPT values for the cervico‐facial muscles that can be applied to a population of healthy elderly subjects. After 65 years of age, further ageing does not influence PPTs in cervico‐facial muscles whereas female gender has lower PPTs.